Prototype of Off-Grid MHP-PV Hybrid Power Plant - Dina Maizana; Surya Akmal; Regi Wando Pratama Siregar (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
Micro Hydro Power Plants (MHP) and Solar Power Plants (PV) are very potential renewable energy solutions to meet electricity needs in remote areas and areas with minimal access to the national electricity grid. This article discusses the development of a hybrid system prototype that combines MHP and PV in an off-grid configuration to improve the reliability and availability of electricity in areas not covered by the main grid. Through a hybrid approach, this system is able to utilize the advantages of each energy source, such as the continuity of power from water flow and solar energy as an additional resource. This study includes technical design, performance simulation, and efficiency analysis of the prototype.